European and International “Instruments” for Criminal Cooperation – the European Arrest Warrant, the Extradition Warrant and the International Arrest Warrant - Németh, Kata (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
The main objective of this study is to present the key differences between the instruments of international and European cooperation in criminal matters, which determine and significantly influence their effectiveness. Criminal cooperation is perhaps one of the youngest areas in the history of European integration which, despite its early puberty, has developed over the years, albeit with some adolescent stubbornness, into one of the most effective instruments of cooperation between the Justice and Home Affairs agencies of the Member States of the European Union. The study concludes that the current instruments of criminal cooperation have simplified and accelerated surrender procedures, especially in the area of organised crime, at the same time also points out that a number of challenges remain to be addressed, related to the independence of the judiciary and the judicial system in general, the question of mutual recognition as well as the fundamental debates on international and EU law and values, constitutional principles and further harmonisation measures. It also highlights that despite significant efforts, there are still gaps in terms of effectiveness, efficiency and coherence with other measures and the use of digital tools.